Molecularly Imprinted Polymers for Cell Recognition. Issue 4 (April 2020) - Piletsky, Stanislav; Canfarotta, Francesco; Poma, Alessandro; Bossi, Alessandra Maria; Piletsky, Sergey
Abstract : Since their conception 50 years ago, molecularly imprinted polymers (MIPs) have seen extensive development both in terms of synthetic routes and applications. Cells are perhaps the most challenging target for molecular imprinting. Although early work was based almost entirely around microprinting methods, recent developments have shifted towards epitope imprinting to generate MIP nanoparticles (NPs). Simultaneously, the development of techniques such as solid phase MIP synthesis has solved many historic issues of MIP production. This review briefly describes various approaches used in cell imprinting with a focus on applications of the created materials in imaging, drug delivery, diagnostics, and tissue engineering. Highlights: Molecular imprinting has been developed for both whole cells and cell epitopes. Molecularly imprinted polymer (MIP) materials have been produced for cell recognition, sorting, and separation. MIP materials are suitable recognition elements for sensor development. MIP materials have been used as scaffolds for tissue engineering. When MIPs are produced in nanoscale formats (nanoMIPs), they are suitable for tissue and cell imaging. NanoMIPs have been developed for drug loading and delivery to specific tissue or cell types.